Analysis of Students' Scientific Literacy Ability in Solving HOTS-Based Chemistry Questions - Debora Putri Sitorus; Iis Siti Jahro (Universitas Negeri Medan, 2024)
Students' scientific literacy abilities are relatively low; apart from that, students are not yet accustomed to solving HOTS-based chemistry science literacy questions, especially in content, context, and science competency. This research aims to analyze the distribution of students' scientific literacy abilities in content, context, and competency. The instruments used are reasoned multiple-choice tests and essays. This research used quantitative descriptive research with a sample of all class XI Science students at SMA Negeri 2 Percut Sei Tuan for the 2023/2024 academic year. The results of data analysis show that the distribution of students' scientific literacy abilities in the content aspect is 71.33% in the content domain in the medium category, the procedural domain 57.11%, and the epistemic domain 56.99% in the low category. The distribution in the context aspect of the health domain was 66.08% in the medium category; the natural resources domain is 48.25%, and the environmental domain is 42.66%, which is in the deficient category. Moreover, the distribution in the domain competency aspect of explaining scientific phenomena is 55.13% in the low category; the domain of evaluating and designing investigations is 44.64%, and the domain of interpreting data and evidence scientifically is 46.68% in the deficient category.